Employee Engagement among Millennial and Generation Z Employees: A Social Exchange Theory Perspective - Yuniasanti, Reny; Kuncoro, Muhammad Wahyu; Fitriana , Nina; Prahara, Sowanya Ardi; Rinaldi , Martaria Rizky (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Millennial and Z generation become the largest productive employee in Indonesia. For the first time in Indonesia's history since Indonesia's independence, one young generation has greatly influenced economic development in Indonesia. They determine where our economy will be taken in the next five years. For that, we must really explore their character and lifestyle, so as not to be a problem for us, one of which is with employee engagement that can maintain the millennial generation in a company / organization. This research is a quantitative study with 121 employees as the participants that selected through purposive sampling. Data analysis will be carried out using multiple regression with Jamovi. The research results show that  millennial employees have social support through online social media, which significantly impacts employee engagement. Apart from that, research results show that  interactional justice not significantly affect on millennial and Z employees' engagement. Based on the statistical analysis results using Jamovi, simultaneously, interactional justice and social support via online social media will have a significant favorable influence on employee engagement among millennial and Z employees. The findings of this research will provide information on the management of millennial and Z employees in the world of work by increasing interaction and social support for companies and co-workers through social media.